Preparation method of Au NSs / TiO2 nano composite material with different coating thicknesses
By adjusting the addition amount of CTAB and PAA ligands, adjusting the titanium dioxide coating thickness, and forming a core-shell structure, the problem of the inability to adjust the degree of bare leakage of gold nanostars in traditional methods is solved, achieving stronger photocatalytic performance and simple preparation. process.
Patent Information
- Application Number
- CN202411451376.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-21
AI Technical Summary
The core-shell structure of traditional titanium dioxide and gold nanostar particles cannot adjust the degree of naked leakage of gold nanostars, limiting the performance of surface plasmon resonance effects, resulting in poor visible light response and long reaction time.
By adjusting the addition amounts of CTAB and PAA ligands, different degrees of competitive binding are achieved, thereby adjusting the coating thickness of titanium dioxide to form a core-shell structure and achieve selective deposition of TiO2.
This method improves the photocatalytic effect of Au NSs/TiO2 nanocomposites, has stronger photoresponsiveness, has a simple preparation process and short reaction time.
Smart Images

Figure HDA0005089242980000011 
Figure HDA0005089242980000012 
Figure HDA0005089242980000021
Abstract
Description
Technical Field
[0001] The present invention relates to the functional partitioning of the Au NSs surface driven by the competitive coordination of ligands on the Au NSs. 2 Selective deposition. Technical Background
[0002] Due to the outstanding properties of the combination of semiconductor and noble metal nanoparticles, people have applied this composite material in many aspects. In particular, hydrogen energy, as an efficient and clean energy source, has the advantages of being storable and renewable, and has the highest energy density (142MJ·kg -1 ), is a research hotspot for alleviating energy shortage and environmental pollution. Using photocatalytic decomposition of water to produce hydrogen is one of the most ideal ways to fundamentally solve energy and environmental problems. People are increasingly interested in the research of photocatalytic hydrogen production.
[0003] Because of their unique properties and irreplaceable catalytic activity, noble metals are often used in photocatalytic materials such as degradation, sensing, and detection. In particular, the surface plasmon resonance (SPR) of noble metal nanoparticles (NSs) can effectively enhance visible light and near-infrared absorption and generate SPR hot electrons. Based on the excellent properties of noble metal nanoparticles, people have made many applications. The resonance wavelength and intensity of surface plasmon resonance depend on the properties of the metal, the size and shape of the metal nanostructure. In recent years, people have done a lot of research on the shape and size of noble metal nanoparticles. Among them, nanostars are a relatively special nanoparticle, whose characteristic morphology is multiple sharp branches extending from the central core. The presence of sharp edges and tips on nanoparticles forms a concentration of electric field during local surface plasmon resonance. The local electric field can be several orders of magnitude higher than other forms (such as nanospheres, nanobipyramids or nanorods). This feature makes nanostars have good application prospects in photocatalysis.
[0004] Since the first report of TiO in 1972 2 Since the photocatalytic decomposition of water, the research on semiconductor photocatalysis has made remarkable progress. Due to its high relative abundance, low cost, and well-arranged valence band and conduction band characteristics, TiO 2 TiO is considered an ideal semiconductor for a variety of applications, especially in the reduction and oxidation half reactions of water splitting. 2 The band gap of gold nanoparticles is around 3.2eV, which requires ultraviolet radiation. People began to study the combination of titanium dioxide with other precious metals, expanding the application conditions of titanium dioxide from ultraviolet light to visible light. When subdivided into several nanometers, gold nanoparticles show significant catalytic activity. Moreover, Au / TiO 2Nanostars have been established as one of the most important model photocatalysts for oxidation and reduction reactions. 2 When combined, the photocatalytic efficiency of the semiconductor under visible light can be significantly improved.
[0005] In order to improve the catalytic performance of precious metal nanoparticles and semiconductor composites, people have also studied the combination of different nanoparticles and semiconductors. Among them, incomplete semiconductor-coated precious metal nanoparticles with Janus as the typical structure have better catalytic performance than other combination forms. Summary of the invention
[0006] The present invention provides an Au NSs / TiO 2 The method for preparing the nanocomposite material has a simple preparation process, a short reaction time and a greater photocatalytic effect than the traditional method.
[0007] The present invention has different titanium dioxide coating thickness Au NSs / TiO 2 The method for preparing a nanocomposite material comprises the following steps:
[0008] 1. Gold nanoseeds: 9 mL of deionized water was placed in a three-necked flask, 1 mL of 0.01 M chloroauric acid aqueous solution was added under vigorous stirring, and the solution was placed in an oil bath and heated to boiling; the oil bath temperature was set to 140°C; after boiling, 1.5 ml of 1 wt% sodium citrate aqueous solution was added thereto, heating was stopped after 15 min, and the solution was stirred in the oil bath and cooled to room temperature; during the experiment, the solution changed from colorless to black and finally to wine red, proving that the gold nanoseeds were successfully synthesized; the obtained gold nanoseed aqueous solution was placed in a 50 mL centrifuge tube and centrifuged once for purification, and the residue at the bottom was placed in a refrigerator after removing the supernatant;
[0009] 2. Preparation of Au NSs: Take 9 mL of deionized water in a conical flask, add 1 mL of 0.01 M chloroauric acid aqueous solution under vigorous stirring, take 40 μL of 1 M hydrochloric acid and add it to the conical flask to make the solution acidic; take 2.5 μL of the gold nanoseeds obtained in step 1 and add them to the conical flask, take 400 μL of 3 mM silver nitrate aqueous solution and 200 μL of 0.1 M ascorbic acid aqueous solution and add them to the system one after the other quickly, and add 2 mL of 2 M CTAB aqueous solution after 30 seconds. The solution changes from transparent light yellow to dark blue, proving that AuNSs are successfully prepared;
[0010] 3. Au NSs@TiO 2Preparation: The Au NSs aqueous solution obtained in step 2 was purified and collected by centrifugation at 8000 rpm / min in deionized water for three times, each time for 10 min, and finally dispersed in 25 mL of deionized water. 290 μL of 2 mM CTAB aqueous solution and 220 μL of 1 M NaOH aqueous solution were slowly added under vigorous stirring; then 100 μL of 1:100 TDAA aqueous solution was added in batches, and added dropwise every hour; after reacting at room temperature for 3 h, AuNSs@TiO 2 Core-shell nanocomposite structures;
[0011] 4. Au NSs / TiO 2 Preparation: The Au NSs aqueous solution obtained in step 2 was purified and collected by centrifugation twice with deionized water at 8000rpm / min, each time for 10min, and finally dispersed in 5mL deionized water. 0, 120, 170, 220, 270, 320, 400μL of 0.645M PAA aqueous solution were added to 2.5mL isopropanol solution, and then 500μL of Au NSs aqueous solution centrifuged twice was added under vigorous stirring, and reacted at room temperature for 3h; ammonia water was added to adjust the pH of the system to 9-10, and then 50μL of 10mM TDAA isopropanol solution was slowly added; after reacting at room temperature for 12h, Au NSs / TiO with different degrees of titanium dioxide coating were obtained. 2 Core-shell nanocomposite structures;
[0012] Further, the chloroauric acid described in step 1 is HAuCl 4 ·4H 2 O; the sodium citrate is C 6 H 5 Na 3 O 7 ·2H 2 O; the speed of the violent stirring is 900rpm, the speed of the centrifugation is 7000rpm, the number of centrifugation is 1, and the time is 10min.
[0013] Furthermore, the centrifugal speed in step 2 is 8000 rpm, the number of centrifugation is 3 times, and the time is 10 min.
[0014] Furthermore, the molecular weight Mw of the PAA described in step 3 is 5000.
[0015] Furthermore, the isopropanol described in step 3 is of HPLC grade and has a purity of 99.8%.
[0016] Furthermore, the ammonia water in step three is 25%-28% ammonia water diluted 50 times.
[0017] Furthermore, the stirring speed in step three is 700 rpm.
[0018] Furthermore, the centrifugal speed in step 4 is 8000 rpm, and the number of centrifugation with anhydrous ethanol and deionized water is 2 times, and the time is 10 minutes.
[0019] The titanium dioxide coatings with different thicknesses prepared by the above method can be applied to various photocatalytic reactions.
[0020] Principle of the present invention:
[0021] Because the core-shell structure of traditional titanium dioxide and gold nanostar particles cannot adjust the degree of exposure of gold nanostars, the surface plasmon resonance effect of the tip of the gold nanostar is greatly restricted, and the visible light response effect cannot exert the maximum effect of the combination of the two, has a certain localization, and the reaction time is long. The present invention uses two ligands with different binding strengths with gold nanoparticles to achieve different degrees of competitive binding by adjusting the amount of the two added, thereby achieving TiO 2 The selective deposition of titanium dioxide can achieve the purpose of different thicknesses of gold nanoparticles. This method has a wide range of applications, short reaction time, simple steps, and relatively simple experimental conditions.
[0022] The Au NSs / TiO synthesized in this invention 2 The nanostructures include the traditional Au core fully coated with titanium dioxide and the Au core coated with different thicknesses of TiO 2 The shell layer makes the gold nanostars exposed to varying degrees. The thinner shell provides a shorter diffusion path for the reactants to reach the gold core, retaining the surface plasmon resonance effect of the gold nanostars, and the titanium dioxide shell makes the gold nanostars difficult to deposit. This structure combines the advantages of the core-shell and gold nanostar structures with strong tip electronic effects.
[0023] Beneficial effects of the present invention:
[0024] In the present invention, CTAB has thiol and carboxyl groups (-SH, -COOH), and PAA has carboxyl groups (-COOH), both of which have affinity with gold nanoparticles, but TiO 2 Most of them will selectively deposit on the side of Au NSs with thiol groups. We fixed the amount of CTAB added and increased the amount of PAA added to increase the competitive binding of the two with Au NSs, which in turn led to the formation of titanium dioxide shells of different thicknesses on the surface of gold nanostar particles, showing different degrees of exposure at the tip of the gold nanostar core to form a core-shell structure. This method is more efficient than the traditional method of fully coating AuNSs@TiO 2 The photocatalytic effect is more obvious and has stronger light response performance. Moreover, core-shell structures with different titanium dioxide shell thicknesses can be easily prepared simply by adjusting the amount of ligand added.
[0025] The core-shell structure prepared by the method has uniform particle size, good dispersibility, simple preparation method, simple experimental conditions and operation, and is short in time, and the yield is also larger than that of traditional synthesis methods. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 Au NSs and fully coated nanostructured Au NSs@TiO 2 and partially coated with Au NSs / TiO 2 UV-Vis spectrum;
[0027] Figure 2 The Au NSs@TiO nanostructure is fully coated 2 and partially coated with Au NSs / TiO 2 XRD pattern of
[0028] Figure 3 The nanostructured Au NSs / TiO obtained by adding PAA in the following amounts: 0 μL, 70 μL, 120 μL, 170 μL, 220 μL, 270 μL, 320 μL, and 400 μL 2 SEM images of
[0029] Figure 4 The nanostructured Au NSs / TiO obtained by adding PAA in the following amounts: 0 μL, 220 μL, and 400 μL. 2 Photocatalytic hydrogen production diagram. DETAILED DESCRIPTION
[0030] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes the implementation modes between the specific implementation modes.
[0031] Specific implementation method: This implementation method is a Au NSs / TiO 2 The method for preparing a nanocomposite material comprises the following steps:
[0032] 1. Gold nanoseeds: 9 mL of deionized water was placed in a three-necked flask, 1 mL of 0.01 M chloroauric acid aqueous solution was added under vigorous stirring, and the solution was placed in an oil bath and heated to boiling; the oil bath temperature was set to 140°C; after boiling, 1.5 ml of 1 wt% sodium citrate aqueous solution was added thereto, heating was stopped after 15 min, and the solution was stirred in the oil bath and cooled to room temperature; during the experiment, the solution changed from colorless to black and finally to wine red, proving that the gold nanoseeds were successfully synthesized; the obtained gold nanoseed aqueous solution was placed in a 50 mL centrifuge tube and centrifuged once for purification, and the residue at the bottom was placed in a refrigerator after removing the supernatant;
[0033] 2. Preparation of Au NSs: Take 9 mL of deionized water in a conical flask, add 1 mL of 0.01 M chloroauric acid aqueous solution under vigorous stirring, take 40 μL of 1 M hydrochloric acid and add it to the conical flask to make the solution acidic; take 2.5 μL of the gold nanoseeds obtained in step 1 and add them to the conical flask, take 400 μL of 3 mM silver nitrate aqueous solution and 200 μL of 0.1 M ascorbic acid aqueous solution and add them to the system one after the other quickly, and add 2 mL of 2 M CTAB aqueous solution after 30 seconds. The solution changes from transparent light yellow to dark blue, proving that Au NSs are successfully prepared;
[0034] 3. Au NSs / TiO 2 Preparation: The Au NSs aqueous solution obtained in step 2 was purified and collected by centrifugation twice with deionized water at 8000rpm / min, each time for 10min, and finally dispersed in 5mL deionized water. 0μL of 0.645M PAA aqueous solution was added to 2.5mL isopropanol solution, and then 500μL of Au NSs aqueous solution after two centrifugations was added under vigorous stirring, and reacted at room temperature for 3h; ammonia water was added to adjust the system pH to 9-10, and then 50μL of 10mM TDAA isopropanol solution was slowly added; after reacting at room temperature for 12h, Au NSs / TiO with different titanium dioxide coating degrees were obtained. 2 Core-shell nanocomposite structures;
[0035] 4. The core-shell structure obtained in step 3 was purified and collected by centrifugation twice with deionized water.
[0036] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the amount of PAA used in step 3 is 70 μL, and the rest is the same as specific implementation method 1.
[0037] Specific implementation method three: This implementation method is different from specific implementation method one in that the amount of PAA used in step three is 120 μL, and the rest is the same as specific implementation method one or two.
[0038] Specific implementation method 4: This implementation method is different from specific implementation method 1 in that the amount of PAA used in step 3 is 170 μL, and the rest is the same as specific implementation methods 1 to 3.
[0039] Specific implementation mode 5: This implementation mode is different from specific implementation mode 1 in that the amount of PAA used in step 3 is 220 μL, and the rest is the same as specific implementation modes 1 to 4.
[0040] Specific implementation method 6: This implementation method is different from specific implementation method 1 in that the amount of PAA used in step 3 is 270 μL, and the rest is the same as specific implementation methods 1 to 5.
[0041] Specific implementation method 7: This implementation method is different from specific implementation method 1 in that the amount of PAA used in step 3 is 320 μL, and the rest is the same as specific implementation methods 1 to 6.
[0042] Specific implementation method eight: This implementation method is different from specific implementation method one in that the amount of PAA used in step three is 400 μL, and the rest is the same as specific implementation methods one to seven.
[0043] The following is a clear and complete description of the technical solution of the present invention, providing a detailed implementation method and a specific operation process. It must be pointed out that for researchers in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the scope of protection of the present invention.
[0044] Embodiment 1:
[0045] 1. Gold nanoseeds: 9 mL of deionized water was placed in a three-necked flask, 1 mL of 0.01 M chloroauric acid aqueous solution was added under vigorous stirring, and the solution was placed in an oil bath and heated to boiling; the oil bath temperature was set to 140°C; after boiling, 1.5 ml of 1 wt% sodium citrate aqueous solution was added thereto, heating was stopped after 15 min, and the solution was stirred in the oil bath and cooled to room temperature; during the experiment, the solution changed from colorless to black and finally to wine red, proving that the gold nanoseeds were successfully synthesized; the obtained gold nanoseed aqueous solution was placed in a 50 mL centrifuge tube and centrifuged once for purification, and the residue at the bottom was placed in a refrigerator after removing the supernatant;
[0046] 2. Preparation of Au NSs: Take 9 mL of deionized water in a conical flask, add 1 mL of 0.01 M chloroauric acid aqueous solution under vigorous stirring, take 40 μL of 1 M hydrochloric acid and add it to the conical flask to make the solution acidic; take 2.5 μL of the gold nanoseeds obtained in step 1 and add them to the conical flask, take 400 μL of 3 mM silver nitrate aqueous solution and 200 μL of 0.1 M ascorbic acid aqueous solution and add them to the system one after the other quickly, and add 2 mL of 2 M CTAB aqueous solution after 30 seconds. The solution changes from transparent light yellow to dark blue, proving that Au NSs are successfully prepared;
[0047] 3. Au NSs / TiO 2 Preparation: The Au NSs aqueous solution obtained in step 2 was purified and collected by centrifugation twice with deionized water at 8000 rpm / min, each time for 10 min, and finally dispersed in 5 mL of deionized water. 0 μL, 220 μL, and 400 μL of 0.645 M PAA aqueous solution were added to 2.5 mL of isopropanol solution and named Au NSs-TiO 2 -1. Au NSs-TiO 2 -2. Au NSs-TiO 2-3, then add 500 μL of Au NSs aqueous solution centrifuged twice under vigorous stirring, and react at room temperature for 3 h; add ammonia water to adjust the pH of the system to 9-10, and then slowly add 50 μL of 10 mM TDAA isopropanol solution; after reacting at room temperature for 12 h, Au NSs / TiO with different titanium dioxide coating degrees can be obtained. 2 Core-shell nanocomposite structures;
[0048] 4. The core-shell structure obtained in step 3 was purified and collected by centrifugation twice with deionized water.
[0049] The Au NSs / TiO prepared in this example 2 The ultraviolet absorption spectrum of the nanocomposite material is shown in Figure 1 As shown. The prepared Au NSs has a large absorption area in the ultraviolet region, with the central absorption peak at 740nm. 2 The central absorption peak of the core-shell structure is at 760nm, and the central absorption peaks of the two are offset by about 20nm. Figure 1
[0050] Embodiment 2:
[0051] 1. Gold nanoseeds: 9 mL of deionized water was placed in a three-necked flask, 1 mL of 0.01 M chloroauric acid aqueous solution was added under vigorous stirring, and the solution was placed in an oil bath and heated to boiling; the oil bath temperature was set to 140°C; after boiling, 1.5 ml of 1 wt% sodium citrate aqueous solution was added thereto, heating was stopped after 15 min, and the solution was stirred in the oil bath and cooled to room temperature; during the experiment, the solution changed from colorless to black and finally to wine red, proving that the gold nanoseeds were successfully synthesized; the obtained gold nanoseed aqueous solution was placed in a 50 mL centrifuge tube and centrifuged once for purification, and the residue at the bottom was placed in a refrigerator after removing the supernatant;
[0052] 2. Preparation of Au NSs: Take 9 mL of deionized water in a conical flask, add 1 mL of 0.01 M chloroauric acid aqueous solution under vigorous stirring, take 40 μL of 1 M hydrochloric acid and add it to the conical flask to make the solution acidic; take 2.5 μL of the gold nanoseeds obtained in step 1 and add them to the conical flask, take 400 μL of 3 mM silver nitrate aqueous solution and 200 μL of 0.1 M ascorbic acid aqueous solution and add them to the system one after the other quickly, and add 2 mL of 2 M CTAB aqueous solution after 30 seconds. The solution changes from transparent light yellow to dark blue, proving that Au NSs are successfully prepared;
[0053] 3. Au NSs@TiO 2Preparation: The Au NSs aqueous solution obtained in step 2 was purified and collected by centrifugation at 8000 rpm / min in deionized water for three times, each time for 10 min, and finally dispersed in 25 mL of deionized water. 290 μL of 2 mM CTAB aqueous solution and 220 μL of 1 M NaOH aqueous solution were slowly added under vigorous stirring; then 100 μL of 1:100 TDAA aqueous solution was added in batches, and it was added dropwise every hour; after reacting at room temperature for 3 h, AuNSs@TiO 2 Core-shell nanocomposite structures;
[0054] 4. The core-shell structure obtained in step 3 was purified and collected by centrifugation twice with deionized water.
[0055] The core-shell Au NSs@TiO prepared in this example 2 The ultraviolet absorption spectrum of the nanocomposite material is shown in Figure 1 As shown. The prepared Au NSs@TiO 2 The central absorption peak of the core-shell structure is at 740nm. Although there is no obvious shift in the central absorption peaks of the two, the optical response range of the core-shell structure is significantly widened.
[0056] Embodiment 3:
[0057] 1. Gold nanoseeds: 9 mL of deionized water was placed in a three-necked flask, 1 mL of 0.01 M chloroauric acid aqueous solution was added under vigorous stirring, and the solution was placed in an oil bath and heated to boiling; the oil bath temperature was set to 140°C; after boiling, 1.5 ml of 1 wt% sodium citrate aqueous solution was added thereto, heating was stopped after 15 min, and the solution was stirred in the oil bath and cooled to room temperature; during the experiment, the solution changed from colorless to black and finally to wine red, proving that the gold nanoseeds were successfully synthesized; the obtained gold nanoseed aqueous solution was placed in a 50 mL centrifuge tube and centrifuged once for purification, and the residue at the bottom was placed in a refrigerator after removing the supernatant;
[0058] 2. Preparation of Au NSs: Take 9 mL of deionized water in a conical flask, add 1 mL of 0.01 M chloroauric acid aqueous solution under vigorous stirring, take 40 μL of 1 M hydrochloric acid and add it to the conical flask to make the solution acidic; take 2.5 μL of the gold nanoseeds obtained in step 1 and add them to the conical flask, take 400 μL of 3 mM silver nitrate aqueous solution and 200 μL of 0.1 M ascorbic acid aqueous solution and add them to the system one after the other quickly, and add 2 mL of 2 M CTAB aqueous solution after 30 seconds. The solution changes from transparent light yellow to dark blue, proving that Au NSs are successfully prepared;
[0059] 3. Au NSs / TiO 2Preparation: The Au NSs aqueous solution obtained in step 2 was purified and collected by centrifugation twice with deionized water at 8000rpm / min, each time for 10min, and finally dispersed in 5mL deionized water. 0, 70, 120, 170, 220, 270, 320, 400μL of 0.645M PAA aqueous solution were added to 2.5mL isopropanol solution, and then 500μL of Au NSs aqueous solution centrifuged twice was added under vigorous stirring, and reacted at room temperature for 3h; ammonia water was added to adjust the pH of the system to 9-10, and then 50μL of 10mM TDAA isopropanol solution was slowly added; after reacting at room temperature for 12h, Au NSs / TiO with different degrees of titanium dioxide coating were obtained. 2 Core-shell nanocomposite structures;
[0060] 4. The core-shell structure obtained in step 3 was purified and collected by centrifugation twice with deionized water. Figure 3
[0061] Embodiment 4:
[0062] 1. Gold nanoseeds: 9 mL of deionized water was placed in a three-necked flask, 1 mL of 0.01 M chloroauric acid aqueous solution was added under vigorous stirring, and the solution was placed in an oil bath and heated to boiling; the oil bath temperature was set to 140°C; after boiling, 1.5 ml of 1 wt% sodium citrate aqueous solution was added thereto, heating was stopped after 15 min, and the solution was stirred in the oil bath and cooled to room temperature; during the experiment, the solution changed from colorless to black and finally to wine red, proving that the gold nanoseeds were successfully synthesized; the obtained gold nanoseed aqueous solution was placed in a 50 mL centrifuge tube and centrifuged once for purification, and the residue at the bottom was placed in a refrigerator after removing the supernatant;
[0063] 2. Preparation of Au NSs: Take 9 mL of deionized water in a conical flask, add 1 mL of 0.01 M chloroauric acid aqueous solution under vigorous stirring, take 40 μL of 1 M hydrochloric acid and add it to the conical flask to make the solution acidic; take 2.5 μL of the gold nanoseeds obtained in step 1 and add them to the conical flask, take 400 μL of 3 mM silver nitrate aqueous solution and 200 μL of 0.1 M ascorbic acid aqueous solution and add them to the system one after the other quickly, and add 2 mL of 2 M CTAB aqueous solution after 30 seconds. The solution changes from transparent light yellow to dark blue, proving that Au NSs are successfully prepared;
[0064] 3. Au NSs@TiO 2Preparation: The Au NSs aqueous solution obtained in step 2 was purified and collected by centrifugation at 8000 rpm / min in deionized water for three times, each time for 10 min, and finally dispersed in 25 mL of deionized water. 290 μL of 2 mM CTAB aqueous solution and 220 μL of 1 M NaOH aqueous solution were slowly added under vigorous stirring; then 100 μL of 1:100 TDAA aqueous solution was added in batches, and added dropwise every hour; after reacting at room temperature for 3 h, Au NSs@TiO 2 Core-shell nanocomposite structures;
[0065] 4. Au NSs / TiO 2 Preparation: The Au NSs aqueous solution obtained in step 2 was purified and collected by centrifugation twice with deionized water at 8000 rpm / min, each time for 10 min, and finally dispersed in 5 mL of deionized water. 0 μL, 220 μL, and 400 μL of 0.645 M PAA aqueous solution were added to 2.5 mL of isopropanol solution and named Au NSs-TiO 2 -1. Au NSs-TiO 2 -2. Au NSs-TiO 2 -3, then add 500 μL of Au NSs aqueous solution centrifuged twice under vigorous stirring, and react at room temperature for 3 h; add ammonia water to adjust the pH of the system to 9-10, and then slowly add 50 μL of 10 mM TDAA isopropanol solution; after reacting at room temperature for 12 h, Au NSs / TiO with different titanium dioxide coating degrees can be obtained. 2 Core-shell nanocomposite structures;
[0066] 5. The core-shell structure obtained in steps 3 and 4 was purified and collected by centrifugation twice with deionized water.
[0067] The Au NSs / TiO prepared in this example 2 and Au NSs@TiO 2 Photocatalytic hydrogen production from nanocomposites Figure 4 As shown in the figure, all four materials have photocatalytic hydrogen production performance, and Au NSs-TiO 2 -2 has the highest hydrogen production efficiency. It can be seen that adjusting the coating thickness of titanium dioxide is significantly helpful to improve the photocatalytic performance of nanomaterials. Figure 4 Hydrogen production effect diagram.
Claims
1. A method for preparing Au NSs / TiO2 nanocomposites with different coating thicknesses, characterized in that: The method comprises the following steps:
1. Gold nanoseeds: 9 mL of deionized water was placed in a three-necked flask, 1 mL of 0.01 M chloroauric acid aqueous solution was added under vigorous stirring, and the solution was placed in an oil bath and heated to boiling; the oil bath temperature was set to 140°C; after boiling, 1.5 ml of 1 wt% sodium citrate aqueous solution was added thereto, heating was stopped after 15 min, and the solution was stirred in the oil bath and cooled to room temperature; during the experiment, the solution changed from colorless to black and finally to wine red, proving that the gold nanoseeds were successfully synthesized; the obtained gold nanoseed aqueous solution was placed in a 50 mL centrifuge tube and centrifuged once for purification, and the residue at the bottom was placed in a refrigerator after removing the supernatant; 2. Preparation of AuNSs: Take 9 mL of deionized water in a conical flask, add 1 mL of 0.01 M chloroauric acid aqueous solution under vigorous stirring, take 40 μL of 1 M hydrochloric acid and add it to the conical flask to make the solution acidic; take 2.5 μL of the gold nanoseeds obtained in step 1 and add them to the conical flask, take 400 μL of 3 mM silver nitrate aqueous solution and 200 μL of 0.1 M ascorbic acid aqueous solution and add them to the system one after the other quickly, and add 2 mL of 2 M CTAB aqueous solution after 30 seconds. The solution changes from transparent light yellow to dark blue, proving that AuNSs are successfully prepared; 3. Preparation of AuNSs@TiO2: The AuNSs aqueous solution obtained in step 2 was purified and collected by centrifugation with deionized water three times, each time for 10 minutes, and finally dispersed in 25 mL of deionized water. 290 μL of 2 mM CTAB aqueous solution and 220 μL of 1 M NaOH aqueous solution were slowly added under vigorous stirring; then 100 μL of 1:100 TDAA aqueous solution was added in batches, and added dropwise every hour; after reacting at room temperature for 3 hours, the Au NSs@TiO2 core-shell nanocomposite structure was obtained; 4. Preparation of AuNSs / TiO2: The AuNSs aqueous solution obtained in step 2 was diluted with 8000 deionized water. The purified product was collected by centrifugation at rpm / min twice, each time for 10 min, and finally dispersed in 5 mL of deionized water. 0, 120, 170, 220, 270, 320, 400 μL of 0.645 M PAA aqueous solution were added to 2.5 mL isopropanol solution, and then 500 μL of Au NSs aqueous solution centrifuged twice was added under vigorous stirring, and the reaction was carried out at room temperature for 3 h; ammonia water was added to adjust the pH of the system to 9-10, and then 50 μL of 10 mM TDAA isopropanol solution was slowly added dropwise; after reacting at room temperature for 12 h, Au NSs / TiO2 core-shell nanocomposite structures with different degrees of titanium dioxide coating were obtained; 5. The nanostructures obtained in steps 3 and 4 were purified and collected by centrifugation twice with deionized water, each time for 10 minutes.
2. The method for preparing a AuNSs@TiO2 nanocomposite material coated with different titanium dioxide thicknesses according to claim 1, characterized in that: The chloroauric acid described in step 1 is HAuCl4·4H2O; the sodium citrate described is C6H5Na3O7·2H2O; the speed of the vigorous stirring is 900 rpm, the speed of the centrifugation is 7000 rpm, the number of centrifugation is 1, and the time is 10 min.
3. The rotation speed of the vigorous stirring described in step 2 according to claim 1 or 2 is 900 rpm.
4. The centrifugal speed in step 3 according to claim 3 is 7000 rpm, the number of centrifugation is 3 times, and the time is 10 min.
5. The molecular weight Mw of the PAA in step 4 according to claim 4 is 5000.
6. The isopropanol in step 4 according to claim 5 is of HPLC grade and has a purity of 99.8%.
7. The ammonia water in step 4 according to claim 6 is 25%-28% ammonia water diluted 50 times.
8. The stirring speed in step 4 according to claim 7 is 700 rpm.
9. The centrifugal speed in step 4 according to claim 8 is 8000 rpm, and the centrifugation times with anhydrous ethanol and deionized water are both 2 times, and the time is 10 min.